1998
DOI: 10.1086/305557
|View full text |Cite
|
Sign up to set email alerts
|

High‐Energy Break and Reflection Features in the Seyfert Galaxy MCG +8‐11‐11

Abstract: W e present the resul ts from A SC A and O SSE si m ul taneous observati ons of the Seyfert 1. 5 gal axy M C G + 8-11-11 perform ed i n A ugust{Septem ber 1995. T he A SC A observati ons,spl i ti nto two poi nti ngs of 10 ksec each,i ndi cate a m odest ux i ncrease ( 20% ) i n 3 days,possi bl y correl ated to a softeni ng ofthe 0. 6{9 keV spectrum . T he spectrum obtai ned com bi ni ng data from both the observati ons i s wel ldescri bed by a hard power l aw ( 1: 64 0: 03) absorbed by a col um n densi ty sl i … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…lower limit found with the Suzaku data only, is also in agreement with that measured by BeppoSAX (170 +300 −80 keV: Perola et al 2000) and only marginally inconsistent with OSSE (270 +90 −70 keV: Grandi et al 1998).…”
Section: The Broad-band Fitsupporting
confidence: 89%
See 1 more Smart Citation
“…lower limit found with the Suzaku data only, is also in agreement with that measured by BeppoSAX (170 +300 −80 keV: Perola et al 2000) and only marginally inconsistent with OSSE (270 +90 −70 keV: Grandi et al 1998).…”
Section: The Broad-band Fitsupporting
confidence: 89%
“…In the past 15 years, MCG+8-11-11 has been observed in the X-rays by ASCA (simultaneously with OSSE, Grandi et al 1998), BeppoSAX (Perola et al 2000), and XMM-Newton (Matt et al 2006). Despite significant flux variability (a factor 3 between ASCA and the present Suzaku observation), there is no clear evidence of variations of the spectral shape of the source.…”
Section: Comparison With Previous Observationsmentioning
confidence: 57%
“…The ASCA (Grandi et al 1998) and BeppoSAX (Perola et al 2000) data were well-fitted by a fairly standard model composed of a powerlaw, a warm absorber, a Compton reflection component, and an Fe Kα line. −0.06 × 10 22 cm −2 ) with the temperature of the material fixed at 10 6 K, and an absorption edge at 0.74 keV corresponding to He-like oxygen.…”
Section: Mcg+8-11-11mentioning
confidence: 98%
“…Some of the past studies of MCG +8−11−11 reported the presence of a strong reflection component R = 1−2.5 [5,8,12,13]. Yet, a good statistical constrain was only obtained with XMMNewton data but limited at energies below 10 keV [5] or combined with low effective exposure ISGRI data ( [13], corresponding to the first point in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As simultaneously the veto system of the telescope registered a strong gamma-ray flux, Perotti et al have suggested that the 112 keV line could be due to double-Compton scattering of a 511 keV line source incident on an external cloud. Later CGRO/OSSE observations did not detect the line with an upper limit flux of 0.9 × 10 −4 ph cm −2 s −1 [8] implying that the line, if present, is variable. In the ISGRI data presented here, we do not detect any line at 112 keV.…”
Section: The 112 Kev Linementioning
confidence: 94%